Elaboramos un texto discontinuo - Dominguez Chavez, Vicky Patricia (2018)
In order to develop the skills of production of discontinuous texts in Primary school children it is interesting that they learn in a playful way acoording to their learning. The following session called: “we created a discontinuous text: the infographic” was developed for students of the 5th grade le primary school of the 5th grade of primary school of the I.E “Manuel Segundo del Águila Velásquez” of Rioja. This session aims to ensure that the students can meet their interests and needs, and that with images support achieve a text with an established purpos. Achive the planned work was done as a team, then they developed an infographic for everyone to know about chistmas and thus achive transmit that reading is more entertaining if we present in different formats, this achievement that students of the 5th grade will be mucho more satisfed with their work. The techniques and materials were chosen taking into account the learning rhythm of each boy and girl.